Identifying hidden needs : creating breakthrough products. - Goffin, Keith, ....-; Koners, Ursula, ....-; Lemke, Fred, ....- (Hampshire : Palgrave, 2010)
Too many new products fail. Mainly because new products are hard to differentiate from exisiting products and they don't capture the customer's imagination. The failure is due to a poor understanding of customers' needs. Companies need to take a radical approach to identifying customers' real needs, and this book demonstrates innovative ways to acheive this. From a top author team with a wealth of experience in the industry and the academic field, Identifying Hidden Needs is full of practical examples and case studies on real products and services. From Coca-Cola to Bentley, Procter and Gamble to IKEA, Identifying Hidden Needs explains why these companies have been so successful.
Keywords: 369.1.